1979
DOI: 10.1016/s0006-3495(79)85244-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer in lipid bilayers

Abstract: The quenching of fluorescence due to energy transfer between a dilute, random array of donor and acceptor chromophores in lipid bilayer was measured and compared to theoretical expressions developed to predict the decrease in emission intensity under these circumstances. The observed intensity was found to be the same function of quencher concentration in both planar, multilamellar dispersions and small, spherical vesicles. The degree of quenching was accurately predicted by a simple relation derived in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 25 publications
(24 reference statements)
2
44
0
Order By: Relevance
“…The observed energy transfer was not influenced by a lO-fold dilution of the lipid phase of the membrane with egg lecithin or by changes in the temperature between 6°C and 37°C, but it was abolished by the addition of unlabeled ATPase. Although the data obtained so far support the idea that a major part of the energy transfer occurs within oligomers containing several ATPase molecules, which do not dissociate measurably after lO-fold dilution of the lipid phase, further experiments at widely different ATPase:lipid ratios are necessary to assess accurately the contribution of collision between ATPase molecules in the membrane to the observed energy transfer (153). The abolition of energy transfer within a few minutes after addition of unlabeled ATPase indicates a relatively rapid exchange between unlabeled and labeled ATPase molecules in the oligomers.…”
Section: Fluorescence-energy Transfermentioning
confidence: 75%
“…The observed energy transfer was not influenced by a lO-fold dilution of the lipid phase of the membrane with egg lecithin or by changes in the temperature between 6°C and 37°C, but it was abolished by the addition of unlabeled ATPase. Although the data obtained so far support the idea that a major part of the energy transfer occurs within oligomers containing several ATPase molecules, which do not dissociate measurably after lO-fold dilution of the lipid phase, further experiments at widely different ATPase:lipid ratios are necessary to assess accurately the contribution of collision between ATPase molecules in the membrane to the observed energy transfer (153). The abolition of energy transfer within a few minutes after addition of unlabeled ATPase indicates a relatively rapid exchange between unlabeled and labeled ATPase molecules in the oligomers.…”
Section: Fluorescence-energy Transfermentioning
confidence: 75%
“…The identity and purity of the compounds were confirmed by proton magnetic resonance spectrometry (Bruker WH-DS spectrometer, 90 MHz), by mass spectrometry (AE[ MS 905 spectrometer, 70 eV) and by HPLC. The incorporation of 1,4-DHP derivatives into the lipid bilayer of membrane models was investigated by means of fluorescence method (9,10). Model phospholipid membranes (liposomes) were prepared from egg phosphatidylcholine in 0.01 M phosphate buffer, pH 7.4.…”
Section: Materi Al S and Methodsmentioning
confidence: 99%
“…The theory of FRET on surfaces and membranes has been an active field [55][56][57][58][59][60][61][62][63][64]. Of these references, the work by Wolber and Hudson [56] probably had the most impact.…”
Section: Fret Theory 1965-2012mentioning
confidence: 99%
“…These authors have found an analytical solution of the FRET problem in two dimensions for the case where the orientation factor is independent of the donoracceptor distance and both donors and acceptors are randomly distributed in a plane [56]. In Refs [55][56][57][58][59][60][61][62][63][64], the emphasis is on heterotransfer. Homotransfer allows studying the accumulation of proteins in membranes.…”
Section: Fret Theory 1965-2012mentioning
confidence: 99%